Pengaruh insektisida organik ekstrak daun pepaya dalam pengendalian lalat rumah (Musca domestica) - Budi Arianto; Khairunnisa Khairunnisa; Wiwit Aditama; Zulfikar Zulfikar (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: One of the most common types of fly species is the house fly (Musca domestica). An increase in the fly population is associated with increased diarrhea, dysentery, and cholera. Control of flies by chemical means is no longer recommended because it can cause pollution or damage to the environment or is not environmentally friendly. An alternative to controlling house flies can be done by using anti-fly plants, which have a sharp odor. Papaya leaves contain alkaloids, karpain, papain enzymes, vitamins C and E, saponins, flavonoids, and tannins.Objective: This study aimed to determine the effect of papaya leaf extract (Carica papaya L.) on the control of the housefly (Musca domestica).Method: This type of quasi-experimental research with Completely Randomized Design (CRD). The research location was carried out at the Laboratory of the Department of Environmental Health Poltekkes Aceh Ministry of Health in August 2022. The doses used were 15%, 25%, and 35%. The research object was papaya extract. Samples for each treatment were 15, repeated three times for each test. The serial concentrations used in this study were 15%, 25%, and 35%. Analysis of Variance analyzed data. (ANOVA) one way with 95% CI.Results: The average number of flies that died from the 35% dose was 6,75, and the 15% dose was only 2,9 flies. There was a significant effect on the average number of dead flies with varying doses of papaya leaf extract (p= 0,000). It is necessary to examine the phytochemicals for the content contained in papaya leaf extract, and it can be made in field trials.Conclusion: Papaya (Carica papaya L.) leaf extract at a dose of 35% can be used in controlling houseflies (Musca domestica) by spraying.